Odpowiedzi

  • Użytkownik Zadane
2009-12-10T13:22:49+01:00
4-2=b
3a+7b=1,5

b=2
3a+14=1,5
3a=1,5-14
3a=12,5/3
a= 4,16
b)
5x=4-2y
4x+y=3

y=3-4x
5x=4-2(3-4x)
5x=4-6+8x
5x-8x=-2
-3x=-2
x=2/3
y=3-4*2/3
y=3-8/3
y=9/3-8/3=1/3


c)
6x-3y=9
x+5y= -9,5

x=-9,5-5y
6(-9,5-5y) -3y=9
-57 -30y-3y=9
-33y=66
y=-2
x=-9,5 +10
x=0,5

2009-12-10T13:28:11+01:00
A)
4-2=b
3a+7b=1,5

2=b
3a+7*2=1,5

2=b
3a+14=1,5

2=b
3a=1,5-14

2=b
3a=-12,5

b=2
a=4,16


b)
5x=4-2y
4x+y=3

5x=4-2y
y=3-4x

5x=4-2*(3-4x)
y=3-4x

5x=4-6+8x
y=3-4x

5x-8x=4-6
y=3-4x

-3x=-2
y=3-4x

x=1,5
y=3-4*1.5

x=1,5
y=-3

c)
6x-3y=9
x+5y= -9,5

6x-3y=9
x=-9,5-5y

6*(-9,5-5y)-3y=9
x=-9,5-5y

-57-30y-3y=9
x=-9,5-5y

-30y-3y=9+57
x=-9,5-5y

-33y=66
x=-9,5-5y

y=-2
x=-9,5-5*(-2)

y=2
x=-9,5+10

y=2
x=0,5